Benefit/possibility ratio of implementing interventional radiology in the diagnosis and treatment of malignant neoplasms of the liver and bile ducts in public hospitals in Minas Gerais State, Brazil (Research, Society and Development, 2024)
Introduction: Malignant neoplasms in the liver and biliary tract represent a major public health challenge in Minas Gerais. This study aims to analyze the magnitude of these diseases between 2020 and 2024, highlighting the relevance of interventional radiology in treatment, such as transarterial chemoembolization (TACE) and percutaneous drainage of liver abscesses. Objective: to understand the incidence and epidemiological characteristics of these neoplasms in the state of Minas Gerais, in addition to evaluating the use of interventional radiology techniques in treatment, considering the number of hospitalizations, mortality rates, duration of hospitalizations, and costs. Methodology: The sample consisted of patients diagnosed with malignant neoplasms in the liver and biliary tract in public hospitals in Minas Gerais between 2020 and 2024, according to data from DATA SUS. The analysis focused on issues such as hospitalization rate, mortality, length of hospitalization, and total costs. In addition to a literature review aimed at evaluating the issue. Discussion: The results show that interventional radiology, such as TACE and percutaneous drainage, offers significant clinical benefits, with reduced hospital stay and improved quality of life for patients. These methods are also more cost-effective compared to traditional approaches. Conclusion: The integration of interventional radiology techniques in the treatment of liver neoplasms in Minas Gerais is essential to improve clinical outcomes, optimize resources and reduce mortality. The study reinforces the importance of these technologies in the public health system.